1102 Audit of referrals from occupational health service to public health england national surveillance scheme for occupational exposure to significant bbv. (24th April 2018) - McCarthy, E; Murphy, E
Abstract : Introduction: Newcastle OHS submits data to the voluntary Public Health England (PHE) significant exposures surveillance system (SigOcc). Data from the Eye of the Needle report (2004 – 2013) showed that there were 4830 significant exposures to a blood borne virus (BBV) reported in healthcare workers and that there was an increase in reported numbers over this time period. 1 The audit aim was to review the quality of data contained in forms returned to NewcastleOHS from PHE between January 2010 and December 2015 following initial submissions. Methods: Cycle 1 – A retrospective audit was carried out to analyse the data collected from PHE forms returned between January 2010 and December 2015. Significant exposures were documented on PHE paper forms which were analysed against the above standards Cycle 2 – A prospective audit of data between December 2015 and December 2016 was carried out. Each case was allocated to a clinician who was responsible for reviewing results and completing the forms at 0, 6 and 24 weeks. This data was collected and entered electronically on forms for submission by email Result: Cycle 1– 26 employees had been reported to SigOcc as having had a significant exposure to a BBV detected source. Follow up was completed in 80% Cycle 2– 21 employees had been reported to OHS as having has a significant exposure to a BBV detected source (December 2015 – 16). On review of these exposures, 86% (18) were reported to SigOcc as data indicated a very low risk exposure in 3 cases. Follow up was 100% in cycle 2 Discussion: HIV exposure in cycle 1 of the audit was higher than reported in the Eye of the Needle report at 54%. In cycle 2 the rate was 33%, similar to published studies. There were 14 exposures to HIV reported to SigOcc in the North East in 2014–15. For HIV infection standard reporting levels were based on HIV antibody detection. HIV PCR levels were not always reported (54% had documented viral loads or CD4 counts). Sig Occ recommends referral of all exposures to HIV antibody detected body fluids. This may need review given new treatments and viral suppression. Hepatitis C exposure in cycle 1 of the audit was 34%, increasing to 48% in cycle 2, similar to reported rates. There were 18 reported exposures to Hepatitis C to SigOcc in the North East in 2014– 5 (51%). Hepatitis C PCR was documented in 67% of cases in cycle 1. SigOcc recommend referral of all hepatitis C antibody detected exposure, however this may require review given viral suppression treatment. Hepatitis B exposures were 8% in cycle 1% and 19% in cycle 2. There were 5 reported cases to SigOcc in the North East in 2014 – 15. Hepatitis B testing appears to be more complete with hepatitis B surface antigen levels and viral DNA level available in known exposure cases.